EFEKTIVITAS METODE PEMBELAJARAN PARTISIPATIF TERHADAP HASIL BELAJAR SANTRI KELAS 3 KMI PADA MATA PELAJARAN TARIKH ISLAM DI PONDOK MODERN ARRISALAH PONOROGO - Rini, Fitri Setyo; Zaki, Muhammad; Gattuso, Ahmad Gagah (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This study aims to evaluate the effectiveness of the participatory learning method on the learning outcomes of third-year KMI students in the subject of Islamic History at Pondok Modern Arrisalah Ponorogo. The research method used is a quantitative experiment with a pre-test and post-test design on control and experimental groups. The research sample consists of 60 students randomly divided into two groups: one group received conventional learning methods and the other group used the participatory learning method. Learning outcome data were collected through written tests administered before and after the intervention. Data analysis used a t-test to compare the average score increases between the two groups. The research results show that students taught with the participatory method experienced a significant increase in learning outcomes compared to the control group. The impact of this study indicates that the participatory learning method can enhance students' understanding and engagement in learning Islamic History. In conclusion, the participatory learning method is effective in improving students' learning outcomes, thus it is recommended to be more widely implemented in the educational environment of pesantren.